Analisis Perubahan Garis Pantai Menggunakan Citra Satelit di Sekitar Muara Sungai Meninting Lombok Nusa Tenggara Barat - Najmi Nurgitasari; Eko Pradjoko; Atas Pracoyo (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Shoreline change is a dynamic process influenced by oceanographic condition, hydrodynamics, and sediment distribution in coastal areas. This study aims to analyze shoreline changes around the Meninting River Estuary from 2016 to 2025 using Google Earth imagery and the QSCAT plugin in QGIS. The study area was divided into two segments, namely the northern and southern sides of the estuary, to identify the characteristics of shoreline changes in each segment. The research methodology included multi-temporal image acquisition, image georeferencing and rectification processes, rectification error assessment, shoreline digitization based on the wet and dry boundaries of the coast, tidal correction, and analysis of shoreline changes using the transect method. The analysis employed the Linear Regression Rate (LRR) parameter, which estimates shoreline change trends by applying linear regression to shoreline positions over time along each transect. The results of the Linear Regression Rate (LRR) analysis indicate that the northern side of the estuary is dominated by accretion, characterized by a shift in the shoreline toward the sea and a sediment volume of 13,166.39 m3/year. Meanwhile, the southern side of the estuary is dominated by erosion, with a sediment volume of -10,574.75 m3/year.